The Effectiveness of O2O Strategy on E-Commerce Transactions - Yulius Lie; Robertus Nugroho Perwiro Atmojo; Hery Harjono Muljo (The Winners, 2019)
This research wanted to show the development of e-commerce transaction brought something new to organizations to accelerate their business through online sales. The presence of online marketplace also gave positive impacts for organizations to run online sales. It was undeniable that e-commerce positively contributes to people’s lives, besides the negative side that most people are still reluctant to use it. Online-to-offline (O2O) was a strategy to direct online users to do offline activities in physical stores. With O2O, customers could buy products from the store after researching online, paying online, and picking up product from the store. The research aimed to find out more about factors that influence consumer trust level to do a transaction in online media, as well as to measure the effectiveness of O2O strategy on e-commerce. Furthermore, this research used a quantitative correlation data analysis method on critical factors that influence customer decision in doing ecommerce transaction, with non-experimental research. The research outcome is the overview of the effectiveness feature and O2O strategy that is provided by the online shopping provider in giving a positive influence for consumers to make purchases in e-commerce. This research also reflects how the people respond to the existence of a marketplace that complements its place with O2O service.